Wage Bargaining when Workers Have Fairness Concerns - Jenny Kragl; Martina Gogova (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We analyze optimal labor contracts when the worker is inequity averse towards the employer. Welfare is maximized for an equal sharing rule of surplus between the worker and the firm. That is, profit sharing is optimal even if effort is contractible. If the firm can make a take-it-or leave-it offer, the optimal contract is also state-dependent but always suboptimal with respect to welfare. The reason is that the firm will always pay the worker less than half of the surplus, thereby leading to agency costs due inequity aversion. If the parties bargain over the optimal contract, the optimal division of surplus is more equitable compared to the case with a purely selfish worker. Moreover, the optimal contract with bargaining approaches the welfare-optimal contract as the parties' bargaining power converges. Our results help explain why workers are willing to accept lower wages in times of crisis but demand higher wages in times of economic rise. Moreover, our findings imply that raising the bargaining power of the less powerful party may increase welfare
Keywords: M52; D03; D86; 330